Reconceptualising Student-Centred Leadership in Southeast Asian Schools: A Systematic Review of Practices, Mediating Mechanisms, and Student Outcomes - Suhaimi, Sharifuddin; A Ghani, Muhammad Faizal; Radzi, Norfariza Mohd; Saad, Aisyah Inani bte Mohd; Muhith, Abd. (Journal of Islamic Education Research, 2026)
This study reconceptualises student-centred leadership in Southeast Asian schools by a systematic synthesis of empirical evidence on leadership practices, mediating mechanisms, and student outcomes. Although student-centred leadership has gained policy attention in response to learning inequities, student disengagement, and socio-emotional challenges, research in Southeast Asia remains fragmented across leadership typologies and reform agendas. Guided by the PRISMA framework, this study conducted a systematic literature review of empirical journal articles indexed in Scopus and Web of Science. Database searches conducted in January 2026 identified 2,338 records. Following rigorous screening and eligibility procedures based on predefined inclusion and exclusion criteria, 32 studies published between 2010 and 2025 were included in the qualitative synthesis. Data were analysed using integrative thematic synthesis. The findings indicate that student-centred leadership is not a singular model. Instead, it constitutes a multidimensional constellation of practices encompassing instructional alignment, relational trust-building, ethical climate formation, pedagogical innovation, and sustained teacher professional development. Leadership influence on students is predominantly indirect and operates through mediating mechanisms such as teaching quality, professional learning structures, school climate, and curriculum enactment. These practices are consistently associated with improved student engagement, wellbeing, agency, autonomy, and learning outcomes. However, implementation is frequently constrained by hierarchical governance structures, accountability pressures, uneven teacher readiness, and digital inequality. This study advances a mechanism-based and contextually grounded reconceptualisation of student-centred leadership in Southeast Asia. It strengthens leadership scholarship by foregrounding mediating pathways and decentring Western-dominated typologies, while offering practical and policy implications for leadership preparation, reform alignment, and equity-oriented school improvement.